Assessment of Radiofrequency Ablation Efficacy for Hepatocellular Carcinoma by Histology and Pretransplant Radiology. Issue 1 (4th January 2019) - Serra, Carla; Cucchetti, Alessandro; Felicani, Cristina; Mosconi, Cristina; De Cinque, Antonio; Golfieri, Rita; Andreone, Pietro; Ercolani, Giorgio; Maroni, Lorenzo; Ravaioli, Matteo; D'Errico, Antonia; Pinna, Antonio Daniele; et al.
Abstract : Radiofrequency ablation (RFA) represents a potentially curative option for early‐stage hepatocellular carcinoma (HCC). This study aims at evaluating the histologic response after RFA of small HCCs arising in cirrhosis. Data were reviewed from 78 patients with de novo HCCs who were treated with RFA and subsequently transplanted. The last radiological assessment before liver transplantation (LT) was used for comparison between modified Response Evaluation Criteria in Solid Tumors (mRECIST) and histological findings. A total of 125 de novo HCCs (median diameter, 20 mm) were treated with RFA only in 92 sessions. There were 98 nodules that did not show local recurrence during follow‐up (78.4%), and the remaining were retreated, except 1 because of subsequent LT. On explanted livers, complete pathological response (CPR) was observed in 61.6%, being 76.9% when <2 cm, 55.0% when 2‐3 cm, and 30.8% when >3 cm. Tumors near hepatic vessels had CPR in 50% of patients versus 69.3% for tumors distant from vessels ( P = 0.039). Of the 125 HCCs, 114 had available radiological assessment within a median of 3 months before LT. Complete radiological response, according to mRECIST, was observed in 77.2% of nodules before LT. The Cohen κ was 0.48 (moderate agreement). The overall accuracy was 78.1%. A total of 18 complications were recorded with only 1 graded as major. In conclusion, RFA can provide high CPR for HCC, especially in smaller tumors distant from hepatic veins or portal branches. The agreement between mRECIST and histology is only moderate. Further refinements in radiological assessment are essential to accurately assess the true effectiveness of RFA.